1998
DOI: 10.1177/096368979800700505
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Porcine Hepatocytes with Human Hepatoma (C3A) Cells for Use in a Bioartificial Liver Support System

Abstract: Cells from primary porcine hepatocytes (PPH) and the immortalized human hepatoma cell line C3A are both used in bioartificial liver support systems (BALSS). In this work the viability and metabolic capacity of PPH and C3A cells cultured in different media were compared. Also, because the cells come into direct or indirect contact with human blood components in BALSS, the effects of human complement on survival and functions of the cells was evaluated. For short-term culture, maintenance of PPH viability was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…However, this still remains a theoretical concern because no evidence exists of transmission in trials performed to date. 17 The 2 basic types of human hepatocyte lines are those derived from human tumors 18,19 and those created by immortalizing human hepatocytes. [20][21][22] Tumor-derived line.…”
Section: Human Hepatocyte Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this still remains a theoretical concern because no evidence exists of transmission in trials performed to date. 17 The 2 basic types of human hepatocyte lines are those derived from human tumors 18,19 and those created by immortalizing human hepatocytes. [20][21][22] Tumor-derived line.…”
Section: Human Hepatocyte Cell Linesmentioning
confidence: 99%
“…26 However, compared with primary porcine hepatocytes, the C3A cell line has lower levels of P-450 IA1 activity, ammonia removal, and amino-acid metabolism. 19 Increasing evidence shows that continuous human liver cell lines derived from liver cancers may not conserve all aspects of drug metabolism found in normal cells, further limiting their efficacy. 27 Immortalized cell lines.…”
Section: Human Hepatocyte Cell Linesmentioning
confidence: 99%
“…Two such cell lines, HepG2 and the HepG2 subclone C3A, are commonly used (Kelly and Darlington, 1989). Previous studies have shown that C3A cells, in particular, are capable of producing urea, a finding which has been generally interpreted as indicating the presence of a fully functional urea cycle capable of ammonia detoxification via this specific pathway, and has led to their use in clinically trialled bioartificial devices (Chen et al, 2003;David et al, 2004;Ellis et al, 1996;Filippi et al, 2004;Wang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to primary porcine hepatocytes, C3A has a lower metabolism ability, particularly to ammonia. 31 Mavri-Damelin et al 32 used the labeled N 15 H 4 CL to detect the ammonia removal capacity of C3A and found that the urea generated did not contain the labeled N 15 . By further analysis of reverse transcription polymerase chain reaction ͑RT-PCT͒ and western blotting, the enzymes, ornithine carbamoyl-transferase, and arginase for urea cycle were lacking in C3A, which shows that C3A cells cannot perform the normal ammonia metabolism, instead they produce ammonia through the pathway outside the urea cycle.…”
Section: ͑1͒mentioning
confidence: 99%